EFFECT OF ADVERTISING, SALES PROMOTION, AND MONEY ON BRAND IMAGE AND PURCHASE DECISIONS ON DAIA 900 DETERGENT PRODUCTS IN PEKANBARU CITY - Yanuari, Said; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2019)
Competition in the detergent powder industry for families isincreasingly increasing, this is indicated by the presence of various brands andproduct variants. Like Rinso, Daia, Attack and others. So the company must havevarious strategies to be able to survive in the competition. One product that isfacing this competition is the Daia 900 detergent. To deal with this competition,the company must be able to understand the factors that influence consumerpurchasing decisions. Among those that will be examined are the issues ofAdvertising, Sales Promotion, Wom, and Brand image.The purpose of this study is to analyze the effect of advertising, salespromotion, and WOM on brand image and the decision to buy 900 detergent inhousewives in the city of Pekanbaru. This research was conducted on Housewivesin the City of Pekanbaru with the sample used as many as 200 respondents whoused the 900 Detergent Daia. Data collection techniques used werequestionnaires with a Likert scale. SEM analysis is a hypothesis testing tool usingAMOS 21 and SPSS 17.00 for Windows.Based on the results of the study, there are the Effects of Advertisements,Sales Promotions, and WOMs on Brand images and the 900 Detergent PurchaseDecision on Housewives in Pekanbaru City. Based on the results of these studies,the company must always select the advertising and sales promotion media that are used effectively, and establish positive WOM communication.